Draft Eighth Five Year Plan (1990-95) and Annual Plan (1991-92) Part II — Plan Proposals in Detail Government of Goa - Planning Commission (Planning Commission, 1990)
During 1984-85 it was estimated that for a projected population of 11.78 lakhs the requirement of food grains would be 1.49 lakh tonnes. However, the mid year population estimate showed that the actual population of the State was 11.00 lakhs for which the food requirement was 1.61 lakh tonnes whereas the production of food grains was 1.50 lakh tonnes leaving a shortfall of 11,000 tonnes of food grains.
Government of Goa, Directorate of Planning, Statistics and Evaluation